Budaya Kerja Berwawasan Cinta Lingkungan pada Pengikut Tarekat Qadiriyyah Wa Naqsyabandiyyah Kepulauan Meranti - Masduki Masduki; Toni Hartono (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2013)
means take some effort to address the human spiritual disease. Therefore, it is important to restore (restoration) also farther more important is the emphasis on philosophical solution that focuses